The study of the behavior of Al impurity in ZnO lattice by a fullerene like model - Ovsiannikova, L.I.; Lashkarev, G.V.; Kartuzov, V.V.; Myroniuk, D.V.; Dranchuk, M.V.; Ievtushenko, A.I. (Physics and Chemistry of Solid State, 2021)
The fullerene like Zn32Al4O36 clusters were investigated and the oxygen interstitial Oi acceptor intrinsic defect formation energy as well as Al ionization energy were calculated. The effect of lattice packing defects on the electroactivity of Al impurity was investigated. Analysis of the defects formation energies shows the smaller formation energy of interstitial Oi in a comparison with a formation of Zn vacancy. This allows us to formulate recommendations of technological conditions for films deposition, with improved electroactivity of Al donor.